2006
DOI: 10.1590/s0100-40422006000200033
|View full text |Cite
|
Sign up to set email alerts
|

Quimioluminiscencia electrogenerada del luminol usando electrodos de bajo costo

Abstract: Recebido em 20/10/04; aceito em 6/6/05; publicado na web em 25/11/05 ELECTROGENERATED CHEMILUMINESCENCE OF LUMINOL USING LOW-COST ELECTRODES. The purpose of the study was to observe eletrogenerated chemiluminescence (ECL) of luminol using different materials as electrodes such as wires, nails, coins, razor blades, etc. Based on the experimental observations and the mechanisms proposed in the literature, students should be capable of analyzing their results in order to understand the phenomena studied. Students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In alkaline medium, luminol is electrochemically oxidized to diazaquinone at 0.5 V on the screen-printed graphite electrode and reacts with hydrogen peroxide produced by atmospheric lactate oxidation catalyzed by LOx giving a luminescent emission. 21,53 If the medium is more alkaline, a higher emission is obtained, due to an increase in luminol deprotonation, 46,54,55 as shown in Fig. 5A.…”
Section: Ecl Mechanismmentioning
confidence: 94%
“…In alkaline medium, luminol is electrochemically oxidized to diazaquinone at 0.5 V on the screen-printed graphite electrode and reacts with hydrogen peroxide produced by atmospheric lactate oxidation catalyzed by LOx giving a luminescent emission. 21,53 If the medium is more alkaline, a higher emission is obtained, due to an increase in luminol deprotonation, 46,54,55 as shown in Fig. 5A.…”
Section: Ecl Mechanismmentioning
confidence: 94%
“…If the medium is more alkaline, a higher emission is obtained, due to an increase in luminol deprotonation [ 30 - 32 ]. In the absence of lactate, a background ECL signal is observed that starts to grow from pH 9.0 up to 10.5 (the background ECL signal increases 206.3 V/s per pH unit).…”
Section: Resultsmentioning
confidence: 99%